The Effectiveness of Derivative Actions as a Means of Protecting The Interests of Minority Shareholders in Limited Liability Companies - Mardiana, Mardiana; Muslimah, Nun Fadillah; Tombi, Johan Tri Noval Hendrian (PT. Anagata Sembagi Education, 2025)
This study examines Derivative Actions as a legal instrument to protect minority shareholders in Limited Liability Companies in Indonesia based on Law Number 40 of 2007. The main issue discussed is the effectiveness of Derivative Actions in ensuring fairness and balance of power between majority and minority shareholders. The purpose of this study is to analyze the legal framework of Derivative Actions in the Indonesian corporate legal system and evaluate its relevance to the application of Good Corporate Governance (GCG) principles. This study uses a normative (doctrinal) legal method with a juridical, conceptual, and case approach. Data was collected from primary, secondary, and tertiary legal materials and analyzed qualitatively through legal interpretation. The findings show that Derivative Actions provide a solid legal basis for minority shareholders to sue Directors or Commissioners who violate their fiduciary duties; however, their practical application is still limited due to procedural complexity and lack of legal awareness. This study concludes that Derivative Actions play a vital role in realizing corporate justice, improving management accountability, and strengthening transparency and responsibility in corporate governance in Indonesia.